The evolutionary basis of elevated testosterone in women with polycystic ovary syndrome: an overview of systematic reviews of the evidence - Bushell, Aiden; Crespi, Bernard J. (Frontiers in Reproductive Health, 2024)
Polycystic ovary syndrome (PCOS) exhibits high prevalence and heritability despite causing negative impacts on fertility and fecundity. Previous hypotheses have postulated that some PCOS-associated traits, especially above-average levels of testosterone, were associated with benefits in ancestral environments. As such, PCOS would represent, in part, a maladaptive extreme of adaptations related to relatively high testosterone. To evaluate this hypothesis, we conducted a series of systematic literature reviews on the associations of testosterone levels, and prenatal testosterone metrics, with measures of strength, robustness, muscularity, and athleticism in females. We also systematically reviewed the literature on associations of testosterone with dominance in females and reviewed archaeological evidence concerning female strength and muscularity and its correlates. The main findings were fivefold: (1) elevated testosterone levels were generally associated with higher strength, muscularity and athleticism in females; (2) females with PCOS showed notable evidence of increased strength, muscularity, and athleticism compared to controls; (3) females with higher testosterone levels exhibited clear evidence of high dominance, (4) despite evidence that higher testosterone is linked with higher bone mineral density in healthy females, PCOS was not clearly associated with this phenotype; and (5) archaeological evidence from osteology, and data from some current small-scale societies, indicated that females often exhibit substantial levels of muscularity. Overall, the hypothesis that relatively high levels of testosterone are associated with benefits to females in some contexts was largely supported. These results provide evidence for the “maladaptive extremes of adaptation” model, with implications for treatment of females with PCOS and for future research.